A simulator-based study of human factors in maritime associated with errors and failures during navigation - Lee, Jian Wei (2017)
Many studies have shown that the majority of accidents/incidents are attributed to human error as the initiating cause. The maritime domain has been relatively slow in recognising the relevance of human factors studies, evident by the limited amount of detailed studies on the subject. This project aims to study the human factors in maritime associated with errors and failures during navigation using a full-scale ship simulator. An electroencephalogram (EEG) – a brain based state monitoring tool has been used to reflect the brain activity of the subject. As such, the brain states such as mental workload, emotion and stress of the cadets can be monitored when they perform tasks in the simulators. The assessment is carried out to compare and contrast 3 different subject EEG results with and without the involvement of a captain. Hypothesis suggested that the subject will be experiencing negative emotion, high workload and stress level when carry out the assessment with a captain under the power distance context, or even the capabilities and rank differences. The study will be including the correlations of human related errors and factors which affected their performance, evaluate together with the collected data. Python and MatLab are used to process the raw data which will then be analyzed using systematic and proven approach. Next, the subject stress levels are estimated, then undergone statistical analysis and a second-by-second analysis. It has been found out that the results from the second-by-second analysis correlates with the simulated situations, further validated the utility of EEG technology in the demanding maritime environment. Undoubtedly, the use of EEG in this project can be made to validate the accuracy of the assessment, identify the suitability of cadets for seagoing duties and propose a robust training matrix or framework for the centre to run future assessment on the cadets. This framework will have a database of thresholds that would have been collated as part of the sample experiments, so that to ensure the quality of assessment and serve as a guide to choose between competent and incompetent cadets. Ultimately, our hypothesis deduced will be arguably testified.